2000
DOI: 10.7863/jum.2000.19.8.511
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler sonography of normal cervical lymph nodes.

Abstract: This study was undertaken to investigate the vascular patterns and resistance of normal cervical nodes by power Doppler sonography. In 101 subjects who had a sonographic examination of the neck, 1050 lymph nodes were detected. Only central vascularity was found in normal cervical nodes. The degree of vascularity in submental and submandibular nodes was higher than that in other regional nodes. Submental nodes had a higher vascular resistance in association with a lower blood flow velocity than other regional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 23 publications
(19 reference statements)
1
34
0
2
Order By: Relevance
“…Published studies on color and power Doppler of normal lymph nodes have reported the visualization of the hilar vessels and, on occasion, visualization of the principal perihilar branches. 9,11,12 In a recent study of normal cervical lymph nodes, Ying et al 11 found no vascularity in more than half of the nodes that had a maximum transverse diameter between 2 and 4 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies on color and power Doppler of normal lymph nodes have reported the visualization of the hilar vessels and, on occasion, visualization of the principal perihilar branches. 9,11,12 In a recent study of normal cervical lymph nodes, Ying et al 11 found no vascularity in more than half of the nodes that had a maximum transverse diameter between 2 and 4 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors [1,2,3,4,5] have suggested use of power Doppler sonography for the differential diagnosis of lymphadenopathies. They maintain that power Doppler sonography displays tiny intranodal vessels better than color Doppler sonography; however, there are no studies which prove this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Normal nodes predominantly have hilar vascularity or are avascular. 16 The occurrence of vascularity in normal nodes increases with increasing size, and about 90% of normal nodes with maximum transverse diameters greater than 5 mm show hilar vascularity. 17 Reactive nodes tend to have prominent hilar vascularity 15,18 because of an increase in vessel diameter and blood flow.…”
Section: 1011mentioning
confidence: 99%